PENGARUH KEMANDIRIAN DAERAH, INVESTASI PEMERINTAH, ANGKATAN KERJA DAN PENDAPATAN PERKAPITA TERHADAP PERTUMBUHAN EKONOMI DAERAH DI 33 PROFINSI TAHUN 2008 – 2013 - Mafizatun Nurhayati (Jurnal Ilmiah Manajemen dan Bisnis, 2015)
This study aimed to analyze the influence of fiscal independence, government investment, labor force and income per capita to economic growth regions in 33 provinces in 2008-2013. Methods of data analysis using multiple linear regression analysis. The results showed that the positive effect on the fiscal autonomy of regional economic growth. Local government investment positive effect on regional economic growth. Regional per capita income does not affect the economic growth of the region. The labor force does not affect the economic growth of the region.  Keywords: economic growth, fiscal independence, the government investment, per capita income, labor force.